2016
DOI: 10.18632/oncotarget.10725
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of heme oxygenase-1 attenuates the negative impact of Ikaros isoform 6 in adult BCR-ABL1-positive B-ALL

Abstract: The correlation between Heme oxygenase-1 (HO-1) and dominant-negative Ikaros isoform 6 (IK6) is unclear. Firstly, we detected that IK6 existed in 20 of 42 (47.6%) adult BCR-ABL1-positive B-lineage acute lymphoblastic leukemia (BCR-ABL1-positive B-ALL) by using reverse transcribed polymerase chain reaction (PCR) and nucleotide sequencing. IK6-positive patients had an unfavorable outcome compared with IK6-negative ones. Further study showed that the level of HO-1 expression was higher in IK6-positive patients’ s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…HO-1 is an essential survival factor for BCR-ABL1-positive B-ALL, the overexpression of which can enhance the resistance to tyrosine kinase inhibitors. 32 However, the We have previously reported that the resistance of chronic myeloid leukemia to imatinib was mediated by HO-1 overexpression in BMSCs based on increase of SDF-1 secretion. Moreover, HO-1 protected BMSCs from ROS through secreting IL-10 in the case of iron overload.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…HO-1 is an essential survival factor for BCR-ABL1-positive B-ALL, the overexpression of which can enhance the resistance to tyrosine kinase inhibitors. 32 However, the We have previously reported that the resistance of chronic myeloid leukemia to imatinib was mediated by HO-1 overexpression in BMSCs based on increase of SDF-1 secretion. Moreover, HO-1 protected BMSCs from ROS through secreting IL-10 in the case of iron overload.…”
Section: Discussionmentioning
confidence: 97%
“…HO-1 is an essential survival factor for BCR-ABL1-positive B-ALL, the overexpression of which can enhance the resistance to tyrosine kinase inhibitors. 32 However, the F I G U R E 6 Heme oxygenase-1 (HO-1) overexpression in bone marrow microenvironment induced resistant of B-cell acute lymphoblastic leukemia (B-ALL) in vivo. A, Flow cytometry assay the tumor growing in peripheral blood of NOD/SCID mice were transplanted by testing the ratio of human CD45+ cells in peripheral blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…The transcripts of the dominant-negative isoforms Ik6 and Ik8 were detected by nested RT-PCR, based on the methods described by Iacobucci et al [30,31]. The expected sizes of the PCR products of the Ik8 and Ik6 isoforms are 390 and 255 base pairs, respectively.…”
Section: Analysis Of Ik6 and Ik8 Transcriptsmentioning
confidence: 99%
“…For example, our laboratory studies the role of the cytoprotective enzyme HO-1 in the prevention of various forms of pre-, post-, and intrinsic-renal AKI. The induction of HO-1 expression provides well documented protection against cisplatin-mediated AKI, 63 but systemic induction of this enzyme is of limited utility in patients with cancer because, despite mixed evidence, 64,65 there is fear that systemic pharmacologic induction of HO-1 will promote cancer cell survival and growth. [66][67][68] However, employing US in patients with cancer receiving cisplatin-based chemotherapy to prevent intrinsic renal injury could be achieved by loading MBs with any one of a number of well described HO-1 inducers 69 and achieving renal-specific delivery with US.…”
Section: Us Treatment Of Kidney Diseasementioning
confidence: 99%